Pendidikan Agama Kristen Sebagai Sarana Pembentukan Iman dan Moral Anak Melalui Gaya Belajar Visual, Auditory, Dan Kinesthetic - Fitriani Sa’sing; Fredelia Keyzia; Novince Pagalla’; Agustina Sarce; Ronaldo Stefanus (Pragmatik : Jurnal Rumpun Ilmu Bahasa dan Pendidikan, 2025)
Christian Religious Education (PAK) plays a strategic role in instilling foundational faith and moral values in children from an early age. Through the VAK learning style ( Visual, Auditory, and Kinesthetic). In the context of modern education, PAK functions not only as a medium for delivering biblical teachings but also as a framework for character formation that aligns with children’s developmental needs. This study aims to analyze the role of PAK as a means of shaping faith and moral values, as well as to describe how PAK learning practices strengthen children’s spiritual growth through modeling, habituation, and learning interactions relevant to their daily lives. This qualitative research employs a descriptive approach, with data collected through literature studies, limited observations, and reflections on field experiences. The findings indicate that contextually designed PAK learning significantly influences children’s ways of thinking, behaving, and acting. The integration of school, family, and church further reinforces the impact of PAK as a spiritual foundation and moral guide in everyday life. This study emphasizes that PAK is not merely the transmission of religious content but a process of value internalization that directs children toward a life of faith, strong character, and responsibility.